Релігійне життя Луцька в 1919-1939 рр. - Малеончук, Галина; Maleonchuk, Halyna (Східноєвропейський національний університет імені Лесі Українки, 2014)
Проаналізовано релігійне життя міста в міжвоєнний період. На основі архівних матеріалів охарактеризовано релігійні громади: юдейську, римо-католицьку, православну, інших християнських конфесій. Особливу увагу звернуто на загальні тенденції організації, розвитку та напрями діяльності кожної з релігійних громад.

The article analyzes the religious life of Lutsk in 1919–1939. Based on archival materials is given characteristic of religious communities in the interwar period: Jewish, Roman Catholic, Orthodox and other Christian groups. Investigates the activities of various religious organizations: Lutsk Jewish religious gmina, community organizations (Catholic action, Lutsk Roman Catholic Society, Petro Mohyla Friends of Education of the Orthodox traditions and defense of the Orthodox faith, Lutsk Holy Cross Brotherhood). Particular attention is drawn to the Ukrainian Church Congressthat took place in 1927 in Lutsk and has become one of the stages of revival of the Ukrainian Orthodox Church. The research highlights the role of the Polish government in the development of the religious life of the city: population growth of the Catholic religion, control of other religious congregations of Lutsk.
Religious Life of Lutsk in 1919–1939
Keywords: Друга Річ Посполита; Луцьк; віросповідання; релігійні громади; церква; Second Commonwealth; Lutsk; religion; religious community; church